Targeted Arginine Metabolism Therapy: A Dilemma in Glioma Treatment - Hou, Xiaoshuang; Chen, Sui; Zhang, Po; Guo, Dongsheng; Wang, Baofeng (Frontiers in Oncology, 2022)
Efforts in the treatment of glioma which is the most common primary malignant tumor of the central nervous system, have not shown satisfactory results despite a comprehensive treatment model that combines various treatment methods, including immunotherapy. Cellular metabolism is a determinant of the viability and function of cancer cells as well as immune cells, and the interplay of immune regulation and metabolic reprogramming in tumors has become an active area of research in recent years. From the perspective of metabolism and immunity in the glioma microenvironment, we elaborated on arginine metabolic reprogramming in glioma cells, which leads to a decrease in arginine levels in the tumor microenvironment. Reduced arginine availability significantly inhibits the proliferation, activation, and function of T cells, thereby promoting the establishment of an immunosuppressive microenvironment. Therefore, replenishment of arginine levels to enhance the anti-tumor activity of T cells is a promising strategy for the treatment of glioma. However, due to the lack of expression of argininosuccinate synthase, gliomas are unable to synthesize arginine; thus, they are highly dependent on the availability of arginine in the extracellular environment. This metabolic weakness of glioma has been utilized by researchers to develop arginine deprivation therapy, which 'starves' tumor cells by consuming large amounts of arginine in circulation. Although it has shown good results, this treatment modality that targets arginine metabolism in glioma is controversial. Exploiting a suitable strategy that can not only enhance the antitumor immune response, but also “starve” tumor cells by regulating arginine metabolism to cure glioma will be promising.